Sistem kontrol inventori pemasokan barang Secara Real Time Menggunakan Vendor-Managed Inventory (VMI) dan Short Message Service (SMS) - Turang, Rinaldo; Suseno, Djatmiko Endro (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
This research underlines the urgency of real-time stock replenishment control system for distributors using vendor-managed inventory. It is valuable in improving corporate performance in lowering inventory cost as well as making better customer service due to the cut made in ordering cycle. The system produces real-time information on stock available at the retailing stores. Stock replenishment can then be done by the distributor at the right time. Using Short Message Service (SMS) as a one-way information channel from retailers to their distributor, the data of every transaction of the supervised item are processed by a rule-based forward-chaining inference system to determine the item’s availability in stores. Folowing steps in Rapid Application Development (RAD), the construction of this system takes place through business modeling, data modeling, process modeling of VMI system, then the application is generated and tested as a prototype. The results are: the stock replenishment control system are able to make transactional data at the stores transparent to the distributor, facilitating the continuation in stock delivery. System architecture reduces the time needed to access information about sales on supervised item by using SMS shortcut. This control system developed in stores can be operationally independent from the retailing systems. Rule-based forward-chaining inference technique processes facts on stock variations, resulting in stock replenishment notification such as normal, reserve, and depleted warning. Keywords: VMI, inventory; Stock replenishment; Rule-based reasoning; Forward-chaining system, RAD